Challenges in Diagnosis and Management of Cutaneous Adverse Drug Reaction - Manish Pradhan (Nepal Journal of Dermatology, Venereology & Leprology)
Adverse drug reactions commonly involve the skin and represent a significant proportion of all drug‐induced illnesses. Most of the times, adverse cutaneous reactions are not severe and only a few are fatal. Real incidence of cutaneous adverse drug reaction is not known. Due to rampant and multiple drug use, there is difficulty finding the culprit drug, so diagnosis of adverse drug reaction and management becomes difficult.